How Are Children in Your School District (and School) Performing on South Carolina's Basic Skills Tests? - Southeastern Public Education Program, Columbia, SC.; Southeastern Public Education Program, Columbia, SC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The South Carolina Basic Skills Assessment Program (BSAP), a testing program, presents information to determine how successfully children in individual school districts are achieving the minimum basic skills required by South Carolina law. Each year BSAP tests are given to children entering the first grade and to children in grades 1, 2, 3, 6, 8, and 11. The test for children entering the first grade is the individually administered Cognitive Skills Assessment Battery to determine if children are "ready" to begin first grade work. Reading and mathematics tests are given each spring to children in grades 1, 2, 3, 6, 8, and 11. Writing tests are given each spring only to children in grades 6, 8, and 11. The purpose of these tests is to help teachers identify children's basic skills weaknesses. The test results are used to improve teachers' instruction in the basic skills. A brief explanation informs parents how to interpret the Student Report. (Author/PN)
Availability: Southeastern Public Education Program, 501-1338 Main Street, Columbia, SC 29201 ($3.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Skills; Elementary Secondary Education; Instructional Improvement; Mathematics Skills; Minimum Competency Testing; Reading Skills; State Programs; Test Interpretation; Testing Programs; Writing Skills; Cognitive Skills Assessment Battery -- South Carolina Basic Skills Assessment Program; Guides, Non-Classroom.